The cherry tree - Ikeda, Daisaku; Ikeda, Daisaku; Wildsmith, Brian (New York : Knopf : Distributed by Random House, 1992)
After a war destroys their Japanese village and kills their father, Taichi and Yumiko find hope by nursing a cherry tree through a harsh winter and seeing it blossom into new life.
Publisher's Weekly
Booklist
School Library Journal
4.9
K-3
Keywords: Trees -- Fiction; War -- Fiction; Trees -- Fiction; War -- Fiction; Japan -- Fiction; Japan -- Fiction